PENGARUH SELF EFFICACY MAHASISWI TERHADAP PENEMPATAN PERTAMA PEMBELAJARAN KLINIK KEBIDANAN - Patroni, Rini (Politeknik Kesehatan Kemenkes Bengkulu, 2014)
The problem that ever students feel are field practice condition that can made students adaptation with clinic learninig field, unconfortable between learning teory and practice because there is not self efficacy yet. The objective of this research to explore self efficay with clinic practice realization problem.This study usedqualitativemethodsof datacollection techniquesthroughin-depth interview. Datawere analyzed usingcontent analysis(content analysis).The results of this study indicate the student has no confidence to face difficulties during the ongoing practice of clinical practice and realized that part of the learning process that must be faced . Most students still in doubt do action against patients and to fear to do wrong . students are sure to encounter difficulties during practice because there field practice mentors who can provide guidance for clinical practice of obstetrics, guidance has been implemented by conducting pre and post comperence all actions performed in accordance with the practice competencies. There is still a lack of guidance from the supervisor of education for the arrival not on schedule, the limited time attitude meeting employee who receives student attendance practices, understanding lack CI competencies to be achieved, patients are less variable field so that not all competencies can be achieved and there are differences between theory with the reality on the ground. competence is difficult to achieve delivery and installation pathological IUD and implan contraceptives.